Changes in Female Drosophila Sleep following Mating Are Mediated by SPSN-SAG Neurons. - Garbe, D.S.; Vigderman, A.S.; Moscato, E.; Dove, A.E.; Vecsey, C.G.; Kayser, M.S.; Sehgal, A. (Journal of Biological Rhythms, 2016)
Female Drosophila melanogaster, like many other organisms, exhibit different behavioral repertoires after mating with a male. These postmating responses (PMRs) include increased egg production and laying, increased rejection behavior (avoiding further male advances), decreased longevity, altered gustation and decreased sleep. Sex Peptide (SP), a protein transferred from the male during copulation, is largely responsible for many of these behavioral responses, and acts through a specific circuit to induce rejection behavior and alter dietary preference. However, less is known about the mechanisms and neurons that influence sleep in mated females. In this study, we investigated postmating changes in female sleep across strains and ages and on different media, and report that these changes are robust and relatively consistent under a variety of conditions. We find that female sleep is reduced by male-derived SP acting through the canonical sex peptide receptor (SPR) within the same neurons responsible for altering other PMRs. This circuit includes the SPSN-SAG neurons, whose silencing by DREADD induces postmating behaviors including sleep. Our data are consistent with the idea that mating status is communicated to the central brain through a common circuit that diverges in higher brain centers to modify a collection of postmating sensorimotor processes.